Exploring the Role of Consciousness in the Origin of the Universe and Life: A Hypothesis of a Sentient Creator - Edoardo Jacopo Bruno (Science & Philosophy)
This article aims to highlight how consciousness may be interconnected with topics related to the existence of God, physics, and cosmology. Despite the importance of this relationship, academia has studied consciousness in relation to each of these themes separately, neglecting to consider all four within a unified analysis. The notion of a conscious God is defined as a sentient creative consciousness that may have generated a holographic universe, a universe from nothing, a multiverse, or a cyclic universe as to create life and intelligent beings. The discussion addresses how this conception of God can be confirmed or refuted through various means, such as the presence of potential mathematical codes in the spacetime of the universe, the information contained within the universe and planet Earth, the development of artificial intelligence, and contact with extraterrestrial civilizations. This article demonstrates that science and philosophy can work together to solve the great mysteries of the cosmos that humanity has pondered for centuries.